191k views
4 votes
Which of these shows the result of using the first equation to substitute for y?

Which of these shows the result of using the first equation to substitute for y?-example-1

1 Answer

3 votes

D) 9x=18

Step-by-step explanation

given


\begin{gathered} y=3x\Rightarrow equation(1) \\ 3x+2y=18\Rightarrow equation(2) \end{gathered}

Step 1

substitute the y value from equation (1) into equation(2)

so


\begin{gathered} 3x+2y=18\operatorname{\Rightarrow}equat\imaginaryI on(2) \\ replace \\ 3x+2(3x)=18 \\ 3x+6x=18 \\ add\text{ like terms } \\ 9x=18 \end{gathered}

therefore, the answer is

D) 9x=18

I hope this helps you

User Binwiederhier
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.